How to be patient. The ability to wait for a reward depends on menstrual cycle phase and feedback-related activity - Reimers, Luise; Büchel, Christian; Diekhof, Esther K. (Frontiers in Neuroscience, 2014)
Dopamine (DA) plays a major role in reinforcement learning with increases promoting reward sensitivity (Go learning) while decreases facilitate the avoidance of negative outcomes (NoGo learning). This is also reflected in adaptations of response time: higher levels of DA enhance speeding up to get a reward, whereas lower levels favor slowing down. The steroid hormones estradiol and progesterone have been shown to modulate dopaminergic tone. Here, we tested fourteen women twice during their menstrual cycle, during the follicular (FP) and the luteal phase (LP), applying functional magnetic resonance imaging while they performed a feedback learning task. Subsequent behavioral testing assessed response time preferences with a clock task, in which subjects had to explore the optimal response time (RT) to maximize reward. In the FP subjects displayed a greater learning-related change of their RT than during the LP, when they were required to slow down. Final RTs in the slow condition were also predicted by feedback-related brain activation, but only in the FP. Increased activation of the inferior frontal junction and rostral cingulate zone was thereby predictive of slower and thus better adapted final RTs. Conversely, final RT was faster and less optimal for reward maximization if activation in the ventromedial prefrontal cortex was enhanced. These findings show that hormonal shifts across the menstrual cycle affect adaptation of response speed during reward acquisition with higher RT adjustment in the FP in the condition that requires slowing down. Since high estradiol levels during the FP increase synaptic DA levels, this conforms well to our hypothesis that estradiol supports Go learning at the expense of NoGo learning. Brain-behavior correlations further indicated that the compensatory capacity to counteract the follicular Go bias may be linked to the ability to more effectively monitor action outcomes and suppress bottom-up reward desiring during feedback processing.